Translation and cultural adaptation for Brazil of the Developing Nurses' Thinking model - Rodrigo Jensen; Diná de Almeida Lopes Monteiro da Cruz; Mary Gay Tesoro; Maria Helena Baena de Moraes Lopes (Universidade de São Paulo, 2014)
OBJECTIVES: to translate and culturally adapt to Brazilian Portuguese the Developing Nurses' Thinking model, used as a strategy for teaching clinical reasoning.METHOD: the translation and cultural adaptation were undertaken through initial translation, synthesis of the translations, back-translation, evaluation by a committee of specialists and a pre-test with 33 undergraduate nursing students.RESULTS: the stages of initial translation, synthesis of the translations and back-translation were undertaken satisfactorily, small adjustments being needed. In the evaluation of the translated version by the committee of specialists, all the items obtained agreement over 80% in the first round of evaluation and in the pre-test with the students, so the model was shown to be fit for purpose.CONCLUSION: the use of the model as a complementary strategy in the teaching of diagnostic reasoning is recommended, with a view to the training of nurses who are more aware regarding the diagnostic task and the importance of patient safety.